2023
DOI: 10.1002/adfm.202212861
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic–Organic Hybrid Dielectrics for Energy Conversion: Mechanism, Strategy, and Applications

Abstract: Dielectric materials with higher energy storage and electromagnetic (EM) energy conversion are in high demand to advance electronic devices, military stealth, and mitigate EM wave pollution. Existing dielectric materials for highenergy-storage electronics and dielectric loss electromagnetic wave absorbers are studied toward realizing these goals, each aligned with the current global grand challenges. Libraries of dielectric materials with desirable permittivity, dielectric loss, and/or dielectric breakdown str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 198 publications
(197 reference statements)
0
10
0
Order By: Relevance
“…Previous research has demonstrated that Debye relaxation has a facilitating role in improving MA performance, and the Cole–Cole model is commonly applied to analyze the relaxation process. The relevant formula is as follows , ε r = ε + ε s ε 1 + j 2 π f τ = ε normalj ε where ε r (relative complex permittivity), ε ∞ (dielectric constant at the infinite frequency), ε s (static dielectric constant), and τ (polarization relaxation time) are in the above formula, respectively. So, ε′ and ε can be expressed by the corresponding equations, respectively. ε = ε + ε s ε 1 + false( 2 π f false) 2 τ 2 ε = 2 π f τ ( ε normals ε ) 1 + false( 2 π f false) 2 τ 2 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated that Debye relaxation has a facilitating role in improving MA performance, and the Cole–Cole model is commonly applied to analyze the relaxation process. The relevant formula is as follows , ε r = ε + ε s ε 1 + j 2 π f τ = ε normalj ε where ε r (relative complex permittivity), ε ∞ (dielectric constant at the infinite frequency), ε s (static dielectric constant), and τ (polarization relaxation time) are in the above formula, respectively. So, ε′ and ε can be expressed by the corresponding equations, respectively. ε = ε + ε s ε 1 + false( 2 π f false) 2 τ 2 ε = 2 π f τ ( ε normals ε ) 1 + false( 2 π f false) 2 τ 2 …”
Section: Resultsmentioning
confidence: 99%
“…Previous research has demonstrated that Debye relaxation has a facilitating role in improving MA performance, and the Cole−Cole model is commonly applied to analyze the relaxation process. The relevant formula is as follows 41,42…”
Section: Resultsmentioning
confidence: 99%
“…The H C value may not be accurate, but the relative relationship can be adopted. Due to the increasing Ni content and the FeNi particle's size, the increase of M S and decrease of H C may favor magnetic loss to some degree [27][28][29].…”
Section: Resultsmentioning
confidence: 99%
“…However, with increasing frequency, the response time of dipoles decreases, leading to higher dielectric loss tangents, with conduction loss becoming more significant at high frequencies. [28,29] For materials, lower dielectric loss is preferable. Higher dielectric loss can lead to increased energy dissipation, lower system efficiency, signal distortion in communication systems, release of thermal energy causing overheating of electronic components or devices, and various other issues.…”
Section: Introductionmentioning
confidence: 99%